BOOK REVIEW: «HOW WE LEARN: WHY BRAINS LEARN BETTER THAN ANY MACHINE... FOR NOW» - Dieorditsa, Taiana; Voronina, Maryna (Physical and Mathematical Education, 2023)
Dean, S. (2021). How we learn: Why brains learn better than any machine... for now. Kyiv, Laboratory.Author: Stanislas DehaeneTranslator: Yulia KostyukOriginal title: "How We Learn: Why Brains Learn Better Than Any Machine... for Now"(2020)Year of publication: 2021Number of pages: 288Publisher: Laboratory (https://laboratoria.pro/)
Keywords: learning; brain; Cognitive Neuroscince; Evidence Based Teaching; universal learning mechanisms